Do Social Media, Good Governance, and Public Trust Increase Citizens’ e-Government Participation? Dual Approach of PLS-SEM and fsQCA - Marlan Hutahaean; Ixora Javanisa Eunike; Andri Dayarana K. Silalahi (Human Behavior and Emerging Technologies)
Citizens’ participation in e-government is imperative for the government as it implies citizens’ participation in public policy. Furthermore, how government strategies allocate resources to increase participation in e-government is essential to investigate. Nevertheless, scant literature debates how e-government can facilitate citizen participation as part of the government’s deliberative policy-making process. To fill the gap, this study uses social media, good governance, and trust to predict e-government participation and testing the hypothesis using PLS-SEM and fsQCA on 455 Indonesian participants who have experience with e-government. The results from SEM confirmed that trust in e-government is the principal predictor of achieving citizens’ participation. To achieve citizens’ trust in e-government, the government must consider perceived ease of use and usefulness as critical factors while spreading e-government-related information on social media. At the same time, transparency from the good governance aspect enhances citizens’ trust. The results of fsQCA equip theoretical and practical insights for the government to determine whether citizens have high or low levels of e-government participation. In achieving high e-government participation, trust, information quality, perceived ease of use, and perceived usefulness are necessary. Besides, low participation occurs when information about e-government is absent on social media and do not care about good governance. These findings will assist the government in comprehensively improving public services through social media and good governance.